Mutation of the conserved late element in geminivirus CP promoters abolishes Arabidopsis TCP24 transcription factor binding and decreases H3K27me3 levels on viral chromatin. - Jacqueline Williams; Elizabeth Regedanz; Natalia Lucinda; Alba Ruth Nava Fereira; Gabriela Lacatus; Mary Berger; Nels O'Connell; Tami Coursey; Jianhua Ruan; David M Bisaro; Garry Sunter (PLoS Pathogens)
In geminiviruses belonging to the genus Begomovirus, coat protein (CP) expression depends on viral AL2 protein, which derepresses and activates the CP promoter through sequence elements that lie within the viral intergenic region (IR). However, AL2 does not exhibit sequence-specific DNA binding activity but is instead directed to responsive promoters through interactions with host factors, most likely transcriptional activators and/or repressors. In this study, we describe a repressive plant-specific transcription factor, Arabidopsis thaliana TCP24 (AtTCP24), that interacts with AL2 and recognizes a class II TCP binding site in the CP promoter (GTGGTCCC). This motif corresponds to the previously identified conserved late element (CLE). We also report that histone 3 lysine 27 trimethylation (H3K27me3), an epigenetic mark associated with facultative repression, is enriched over the viral IR. H3K27me3 is deposited by Polycomb Repressive Complex 2 (PRC2), a critical regulator of gene expression and development in plants and animals. Remarkably, mutation of the TCP24 binding site (the CLE) in tomato golden mosaic virus (TGMV) and cabbage leaf curl virus (CaLCuV) CP promoters greatly diminishes H3K27me3 levels on viral chromatin and causes a dramatic delay and attenuation of disease symptoms in infected Arabidopsis and Nicotiana benthamiana plants. Symptom remission is accompanied by decreased viral DNA levels in systemically infected tissue. Nevertheless, in transient replication assays CLE mutation delays but does not limit the accumulation of viral double-stranded DNA, although single-stranded DNA and CP mRNA levels are decreased. These findings suggest that TCP24 binding to the CLE leads to CP promoter repression and H3K27me3 deposition, while TCP24-AL2 interaction may recruit AL2 to derepress and activate the promoter. Thus, a repressive host transcription factor may be repurposed to target a viral factor essential for promoter activity. The presence of the CLE in many begomoviruses suggests a common scheme for late promoter regulation.